Penurunan Reject Kemasan Bottom Powder Kosmetik Dengan Pendekatan Plan, Do, Check, Action Dan Failure Mode And Effects Analysis (FMEA) Di Industri Manufaktur Kosmetik - Ovi Dian Lestari; Rakay Edhiargo Toyosito; Lifia Citra Ramadhanti (Science and Education Journal (SICEDU), 2026)
Product quality is one of the important factors in maintaining customer satisfaction and increasing the competitiveness of cosmetic manufacturing companies. PT PTI, as a cosmetic manufacturing company, still faces problems related to the high number of Rejects in the powder packaging process, especially bottom sticker tearing defects, inject hitting printing defects, and cut bottom sticker defects. The high Reject rate causes decreased production effectiveness, increased material waste, higher production costs, and reduced packaging quality. This study aims to identify the factors causing Rejects in the powder packaging process and to determine improvement proposals to reduce the Reject rate in Powder Division Zone A at PT PTI. The methods used in this study are the Plan, Do, Check, Action (PDCA) approach and Failure Mode and Effect Analysis (FMEA). Data processing was carried out using histograms, Pareto diagrams, fishbone diagrams, and Risk Priority Number (RPN) analysis to determine improvement priorities based on the highest level of failure risk. The research data were obtained from production and Reject data during the W36 to W41 period in 2025 at Line PNP 03 of Powder Division Zone A. The results showed that the dominant Reject type was bottom sticker tearing, with a total Reject of 5,200 pcs or 45.87% of the total Rejects. Based on the FMEA analysis, the highest RPN value obtained was 567 for the bottom sticker tearing defect, making it the main priority for corrective actions. The main causes of the Rejects originated from machine factors, work methods, materials, and operators. The proposed improvements include periodic machine setting inspections, improving operator accuracy, routine machine maintenance, establishing machine setting standards, and increasing supervision in the packaging process. The implementation of the improvements showed a decrease in the number of Rejects in the powder packaging process. By implementing the PDCA and FMEA methods, the company is expected to improve product quality, reduce the number of Rejects, and increase the effectiveness and efficiency of the production process in Powder Division Zone A at PT PTI in a sustainable and optimal manner.